Pengaruh Pemberian Minuman Cokelat (Theobroma cacao L.) Terhadap Berat Basah Organ Hati Tikus Diabetes Melitus - Putri Rahayu Ratri; Adhiningsih Yulianti; Arisanty Nur Setia Restuti (ARTERI : Jurnal Ilmu Kesehatan, 2021)
Cacao (Theobroma cacao L.) is known to have enormous potential advantages because they contain vitamins A1, B1, B2, C, D, and E as well as minerals such as iron, zinc, phosphorus, magnesium, and copper. In addition, chocolate is also known to be rich in active antioxidant ingredients such as phenolic compounds, prociandin, and flavonoids which can reduce the bad effects of antioxidants in the body. giving chocolate to experimental animals and consumption interventions in humans can prevent and overcome the problem of several diseases, one of which is diabetes mellitus. The purpose of this study was to see the effect of giving cocoa powder drink to the wet weight of the liver in rats with diabetes mellitus. The research design used was experimental research using a completely randomized design with a post-test only control group design. The experimental sample used fifteen male white rats (Rattus norvegicus) Sprague Dawley strain. The experimental mice were divided into 5 groups, namely the negative control group (K-), namely normal rats without any treatment, the positive group, namely the diabetes mellitus (K +) group; treatment group 1 (KP1), treatment group 2 (KP2), treatment group 3 (KP3), namely the diabetes mellitus group of rats that were given the treatment of chocolate drink with a concentration of cocoa powder drink doses of 2%, 4% and 6%. Data analysis was performed using the One Way ANOVA test. Results: The results showed that the organ weight in the group K- = 10.46 ± 0.44; K + = 11.49 ± 0.39; KP1 = 9.95 ± 0.60; KP2 = 11.30 ± 0.60; KP3 = 11.09± 0.90. Statistical analysis showed that there was no significant difference for each treatment with a value of p = 0.077. The conclusions in the study regarding the effect of giving chocolate drink on the wet weight of the liver in rats with diabetes mellitus showed that giving cocoa powder with a concentration of 2%, 4% and 6% was not able to significantly affect the wet weight of the liver.